2019
DOI: 10.3390/nu11112636
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Endurance and Resistance Training on Skeletal Muscle Glucose Metabolism in Older Adults

Abstract: Aging is associated with insulin resistance and the development of type 2 diabetes. While this process is multifaceted, age-related changes to skeletal muscle are expected to contribute to impaired glucose metabolism. Some of these changes include sarcopenia, impaired insulin signaling, and imbalances in glucose utilization. Endurance and resistance exercise training have been endorsed as interventions to improve glucose tolerance and whole-body insulin sensitivity in the elderly. While both types of exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 113 publications
(200 reference statements)
4
41
0
Order By: Relevance
“…Here, huddling behavior completely or partially alleviated the increase in glycogen content caused by the decrease in glycogen degradation enzyme in the myocardium of voles following cold environment exposure by increasing glycogen decomposition. Normal glycogen metabolism is the basis of exercise in mammals ( Consitt et al, 2019 ; Moniz et al, 2020 ). Earlier studies on Brandt’s voles showed that activity is higher in huddling groups than separated groups under cool environments ( Sukhchuluun et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, huddling behavior completely or partially alleviated the increase in glycogen content caused by the decrease in glycogen degradation enzyme in the myocardium of voles following cold environment exposure by increasing glycogen decomposition. Normal glycogen metabolism is the basis of exercise in mammals ( Consitt et al, 2019 ; Moniz et al, 2020 ). Earlier studies on Brandt’s voles showed that activity is higher in huddling groups than separated groups under cool environments ( Sukhchuluun et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, huddling behavior completely or partially alleviated the increase in glycogen content caused by the increase in glycogen synthesis in the myocardium of voles following cold environment exposure. Normal glycogen metabolism is the basis of exercise in mammals [39,40]. Earlier studies on Brandt's voles showed that activity is higher in huddling groups than separated groups under cool environments [19].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins involved in glycolysis and glycogen metabolism, as well as GLUT4 protein (the transporter mediating insulin-dependent glucose uptake), are downregulated [ 35 , 36 ]. Moreover, several age-related alterations in skeletal muscle insulin signaling were reported, contributing to systemic insulin resistance and impaired glucose metabolism [ 37 ]. Skeletal muscle lipid accumulation in old age is mostly dependent on alterations in uptake and oxidation.…”
Section: Aging and Skeletal Muscle Qualitymentioning
confidence: 99%